PENGARUH VARIASI KONSENTRASI PEKTIN KULIT BUAH JERUK BALI (Citrus maxima MERR.) SEBAGAI SUSPENDING AGENT TERHADAP SIFAT FISIK SUSPENSI MAGNESIUM HIDROKSIDA - yulias ninik windriyati; ika kurnaningsih; mufrod mufrod (Universitas Wahid Hasyim Semarang, 2008)
ABSTRACTSuspention is the most effective liquid dosage form for magnesium hydroxide because the compound relatively insoluble in water. Pectin as suspending agent has been used to inhibit sedimentation of suspension. The aim of this research is to know physical and chemical characteristic of pectin from Bali Citrus Peels and the influence of difference concentration of pectin and storage duration to physical characteristic of magnesium hydroxide suspensions. Pectin powder was extracted from Bali Citrus Peels with 70% ethanol. Magnesium hidroxide suspensions were made in three formulas with pectin concentration 0.75%, 1.00% and 1.25%. The suspensions was tested for their physical characteristic such as particle sizes, viscosity, sediment volume, redispersibility and fluidity (easiness to be poured) for 4 weeks. The result of this research shown that the pectin from Bali Citrus Peels can be used as suspending agent. The pectin powder has 15.26% water content, pH 3 and no amylum. The viscosity of mucilago was 33.33 cP for 0.75% concentration of pectin, 37.17 cP for 1.00%, and 40.50 cP for 1.25% respectively at the time of preparation. The difference concentration of pectin and its storage duration significantly affected particle sizes, viscosity, redispersibility and fluidity, while sediment volumes had influenced until the end of first week. Keywords: Pectin made of Bali Citrus Peels, Physical Characteristic and Suspensions